2016
DOI: 10.3390/polym8100372
|View full text |Cite
|
Sign up to set email alerts
|

CaLB Catalyzed Conversion of ε-Caprolactone in Aqueous Medium. Part 1: Immobilization of CaLB to Microgels

Abstract: Abstract:The enzymatic ring-opening polymerization of lactones is a method of increasing interest for the synthesis of biodegradable and biocompatible polymers. In the past it was shown that immobilization of Candida antarctica lipase B (CaLB) and the reaction medium play an important role in the polymerization ability especially of medium ring size lactones like ε-caprolactone (ε-CL). We investigated a route for the preparation of compartmentalized microgels based on poly(glycidol) in which CaLB was immobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…[10][11][12][13][14][15][16][17] Due to their versatile properties, microgels find various applications for drug delivery, as biomaterials or in the field of catalysis. [18][19][20] In last-named applications, microgels enable exploring and controlling chemical reactions in compartments, opening new platforms for bio-inspired catalysts. Here, microgels have been investigated as responsive carrier colloids for catalytically active materials, naming metal nanoparticles, metallic complexes, organocatalysts and enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Due to their versatile properties, microgels find various applications for drug delivery, as biomaterials or in the field of catalysis. [18][19][20] In last-named applications, microgels enable exploring and controlling chemical reactions in compartments, opening new platforms for bio-inspired catalysts. Here, microgels have been investigated as responsive carrier colloids for catalytically active materials, naming metal nanoparticles, metallic complexes, organocatalysts and enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the microenvironment of an immobilized enzyme can determine the performance of the enzyme, with regards to its catalytic activity, stability, and selectivity. [7][8][9] In addition, macromolecular crowding and surface charge are important but neglected aspects of the enzyme microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our groups showed the activity effect of CaLB immobilization to tailored microgels of different polarity [ 30 ]. Providing a more hydrophobic environment in the microgel, the hydrolytic activity was reduced, and the polymerization activity was increased.…”
Section: Resultsmentioning
confidence: 99%
“…Hereby, the influence of the gel network on the enzymatic activity and the protection against solvents are important research issues among others [ 25 , 26 , 27 ]. Recently, we reported about the synthesis and immobilization of CaLB in tailormade microgels and showed the influence of the microgel polarity on the ring-opening polymerization activity of CaLB [ 28 , 29 , 30 ]. Besides our work Montanier and colleagues published their work on engineering of CaLB for polyester synthesis [ 31 ].…”
Section: Introductionmentioning
confidence: 99%